Stimulation of the Epithelial Na+ Channel in Renal Principal Cells by Gs-Coupled Designer Receptors Exclusively Activated by Designer Drugs - Soares, Antonio G.; Contreras, Jorge; Archer, Crystal R.; Mironova, Elena; Berdeaux, Rebecca; Stockand, James D.; Abd El-Aziz, Tarek Mohamed (Frontiers in Physiology, 2021)
The activity of the Epithelial Na+ Channel (ENaC) in renal principal cells (PC) fine-tunes sodium excretion and consequently, affects blood pressure. The Gs-adenylyl cyclase-cAMP signal transduction pathway is believed to play a central role in the normal control of ENaC activity in PCs. The current study quantifies the importance of this signaling pathway to the regulation of ENaC activity in vivo using a knock-in mouse that has conditional expression of Gs-DREADD (designer receptors exclusively activated by designer drugs; GsD) in renal PCs. The GsD mouse also contains a cAMP response element-luciferase reporter transgene for non-invasive bioluminescence monitoring of cAMP signaling. Clozapine N-oxide (CNO) was used to selectively and temporally stimulate GsD. Treatment with CNO significantly increased luciferase bioluminescence in the kidneys of PC-specific GsD but not control mice. CNO also significantly increased the activity of ENaC in principal cells in PC-specific GsD mice compared to untreated knock-in mice and CNO treated littermate controls. The cell permeable cAMP analog, 8-(4-chlorophenylthio)adenosine 3′,5′-cyclic monophosphate, significantly increased the activity and expression in the plasma membrane of recombinant ENaC expressed in CHO and COS-7 cells, respectively. Treatment of PC-specific GsD mice with CNO rapidly and significantly decreased urinary Na+ excretion compared to untreated PC-specific GsD mice and treated littermate controls. This decrease in Na+ excretion in response to CNO in PC-specific GsD mice was similar in magnitude and timing as that induced by the selective vasopressin receptor 2 agonist, desmopressin, in wild type mice. These findings demonstrate for the first time that targeted activation of Gs signaling exclusively in PCs is sufficient to increase ENaC activity and decrease dependent urinary Na+ excretion in live animals.